(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Road infrastructure is critical to the economy, providing mobility for people and cargo, and contributing to economic growth. Modern technologies, particularly 3D laser scanning, play a significant role in the monitoring, evaluation, and operation of infrastructure. As part of this study, the AU20 laser scanning system was used to obtain transverse road surface profiles on a certain section of the Yerevan Tbilisi Highway. The scan data was processed in the ArmRef02 coordinate system. The main objectives of the survey are: • develop a methodology to automatically separate the road surface from the 3D point cloud. • Identify the pivotal and central axes of the path through spatial analysis. • Compare the resulting profiles with the technical norms and suggest possible improvements. The results showed that existing technical abnormalities have a negative impact on drainage efficiency and traffic safety. Adherence to local and international regulatory standards can contribute to improved road operation and sustainable development of transport networks.